Organoleptic Assessment, Protein Content, and Fat Content of Broiler Chicken Eggs Soaked in Mangosteen Peel Extract (Garcinia mangostana L.) During Storage - Suwitari, Ni Ketut Etty; Rukmini, Ni Ketut Sri; Janurianti, Ni Made Defy (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
The purpose of this study was to determine the organoleptic assessment, protein content, and fat content of broiler chicken eggs soaked in mangosteen peel extract (Garcinia mangostana L.) during storage. The research design used was a completely randomized design factorial pattern consisting of 2 factors. The first factor was the mangosteen peel extract solution with different concentrations (0%, 5%, 10%, and 15%). The second factor was storage for 0, 1, 2, 3, and 4 weeks. The data obtained were analyzed for diversity using an ANOVA test, and if a significant effect was found (P <0.05), then the analysis continued with Duncan's test. The treatment of mangosteen peel extract concentration level did not affect the protein content, fat content, and organoleptic assessment of chicken eggs. Meanwhile, storage time had a very significant effect (P <0.01) on the protein content and fat content of chicken eggs. The protein content of chicken eggs in the treatment with a mangosteen peel concentration level ranged from 8.43% to 8.58%. The highest protein content was obtained on the 4th day of storage, namely 8.76%. The fat content of chicken eggs ranged from 4.33 to 4.51%. The lowest fat content was obtained on the 4-day storage treatment, namely 4.04%. Soaking chicken eggs in mangosteen peel extract and egg storage for up to 4 weeks did not have a significant effect on the organoleptic properties of chicken eggs. Contribution to Sustainable Development Goals (SDGs):SDG 1: No PovertySDG 2: Zero HungerSDG 3: Good Health and Well-Being